MENACES SUR LA SECURITE DES DONNEES INFORMATIQUES DANS LES ORDINATEURS (Enquête menée à Kindu de Mars à Décembre 2021) - Albert, OMOKENDE OTSHUDI (IJRDO -Journal of Computer Science Engineering, 2022)
The threats of computer data are well and truly felt by users working in both publics and privates organisations in Kindu.The types of mentioned by our respondents are multiple and manifest themselves in different proportions. Howerver, viruses represent 36% of the opinions of our respondent.